PELATIHAN SENI MERANGKAI BUNGA DAN JANUR DI PKK PEDUKUHAN KEMBANGPUTIHAN - Agoestin Kemalawati (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2020)
This community service activity aims to introduce the art of flower arrangement combined with young coconut leaves and how to make it to the PKK member of the Selarong village. Through this activity, participants are expected to know the types of flower arrangement patterns and how to arrange them. PKM activities in the form of training were attended by 25 participants. The details of the activities are: 1) explaining the material using power point media; 2) demonstrating how to arrange flowers according to the design pattern; 3) dividing participants into 5 practice groups accompanied by a companion; 4) distribute flowers, materials and equipment needed; 5) participants practice flower arrangement according to the pattern accompanied by a companion instructor. The result of this activity was that the participants gained insight into various kinds of flower arrangements and how to arrange them.